The Development of Creative Organization Potential in the Context of Intelligent Production - Zelentsova, Lidia; Shalamova, Nataliya; Akopyan, Anna (Տիգրան Մեծ)
This study aims to determine, from the standpoint of the philosophy, the creativity of approach to measuring and specifying the components of the creative potential of an organization to assess its level and further development in the conditions of the intellectualization of modern production. The subject of the study is the interaction of the components of creative potential. The study's hypothesis builds on the problem of the multi-aspect nature of the industrial activity, what in the conditions of digitalization and the use of artificial intelligence requires creativity in various subject areas. Research objectives: to reason the scientific approach of structural and logical „dissection‟ of creative potential to identify its key components; to develop the structure of the creative potential; to determine methods for measuring the components of the creative potential of the organization. The authors proposed a structural and logical model to form and develop creative potential. The integrating module of this model is a four-component creative group of interacting subpotentials, selected by subject-functional areas: subject- functional: intellectual-innovative, industrial-technological, organizational-economical and sociocultural since the results of creativity are concentrated in these areas and can be measured in specially selected indicators.
Keywords: Philosophy of economics